Dynamics of Competitiveness and Determinants of Indonesian Cocoa Exports in The Global Market - Setiawan, Risqi Firdaus; Soedarto, Teguh; Hendrarini, Hamidah; Mubarokah (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Cocoa is a strategic Indonesian plantation commodity that faces challenges in productivity, quality, and global competitiveness, despite being the world's third-largest producer.Purpose: This study aims to analyze the dynamics of Indonesia's cocoa competitiveness and the determinants of cocoa exports in the global market.Design/methodology/approach: This study used secondary data from the BPS, UN Comtrade, FAO, World Bank, and Bank Indonesia. The analysis includes the Trade Specialization Index (ISP), Export Product Dynamics (EPD) to measure the market position, and the Error Correction Model (ECM) to analyze the determinants of exports in the short and long term.Findings/Results: ISP shows Indonesia as a net exporter with an average value of 0.614 and relatively good strength. The EPD classifies the top destination countries of Malaysia, China, the Philippines and India as Rising Stars, indicating strong growth potential. The ECM results show that production, productivity, price, exchange rate, destination countries’ GDP, RCA, and ECI have a significant effect on exports in the long run, emphasizing the role of structural factors. Meanwhile, in the short term, the effect is inconsistent because of market volatility and structural limitations.Conclusion: The findings imply that improving productivity, enhancing quality standards, and strengthening the downstream cocoa industry are crucial for increasing Indonesia’s export competitiveness. These efforts can enhance the country’s comparative advantage and economic complexity, thereby supporting sustainable export growth in the global market.Originality/value (state of the art): The integration of ISP and EPD analyses with export determinants using ECM provides a comprehensive overview and practical policy recommendations for the sustainability of cocoa exports. Keywords: Cocoa, global market, Trade Specialization Index, global competitiveness, cocoa exports